Cold spray deposition of aluminium and aluminium oxide - Liu, Yuman. (2010)
Cold spray technique is a relatively new addition to the Thermal Spray family. It is believed to have potential in manipulating the cold-sprayed coating to perform according to the required physical and chemical properties. The intent of this project is to optimize the parameters for the deposition of pure aluminium and aluminium oxide (87wt%Al2O3-13wt%Al) powders on aluminium substrate using the cold spray technique, so as to construct a multi-layer laminate of Al and Al2O3 coatings. Alternating Al and Al2O3 coatings mimic the architecture of the strong and tough natural material – mollusk shell. The results of this study will aid in the development of new armour materials. The parameters for Al deposition were optimized for higher particle velocity under SprayWatch programme. A study on the effects of temperature on coating quality was done to determine the parameters for deposition of Al2O3. Consistency in the single-layer coatings demonstrated the reproducibility of the system. On the average, the Al coatings displayed a thickness of 97μm, attaining 89%TMD of Al and HV25gf 47 while the Al2O3 coatings were of 418μm, with 77%TMD of the feedstock powder and HV100gf 138. 5-layered laminates were built up with alternating deposition of Al2O3 and Al. The design of hard and soft layers is similar to the ordered structure of mollusk shell. Hardness values of HV100gf 146 and HV25gf 60 were achieved for Al2O3 and Al coatings respectively. Comparison to pure alumina tile and Al-1100 plate were made under 3-point bending test. The mode of failure of the laminates was similar to that of ductile Al plate. While the strength of the laminates (286MPa) is less than that of the alumina tile (1455MPa), the toughness is calculated to be about 6 times higher than the brittle alumina tile.